Heterotypic gap junctions at glutamatergic mixed synapses are abundant in goldfish brain. (29th January 2015) - Rash, J.E.; Kamasawa, N.; Vanderpool, K.G.; Yasumura, T.; O'Brien, J.; Nannapaneni, S.; Pereda, A.E.; Nagy, J.I.
Highlights: Immunocytochemical labeling reveals that neuronal gap junctions are abundant and widely distributed in goldfish brain. Cx35/Cx34.7-containing gap junctions occur primarily at glutamatergic axon terminals, forming excitatory "mixed" synapses. Immunogold labeling for Cx35 was only in axon terminal hemiplaques and for Cx34.7 only in somatic and dendritic hemiplaques. Widespread Cx35:Cx34.7 heterotypic coupling may imply widespread electrical rectification. Abstract: Gap junctions provide for direct intercellular electrical and metabolic coupling. The abundance of gap junctions at "large myelinated club ending (LMCE)" synapses on Mauthner cells (M-cells) of the teleost brain provided a convenient model to correlate anatomical and physiological properties of electrical synapses. There, presynaptic action potentials were found to evoke short-latency electrical "pre-potentials" immediately preceding their accompanying glutamate-induced depolarizations, making these the first unambiguously identified "mixed" (i.e., chemical plus electrical) synapses in the vertebrate CNS. We recently showed that gap junctions at these synapses exhibit asymmetric electrical resistance (i.e., electrical rectification), which we correlated with total molecular asymmetry of connexin composition in their apposing gap junction hemiplaques, with connexin35 (Cx35) restricted to axon terminal hemiplaques and connexin34.7 (Cx34.7) restricted to apposing M-cell plasma membranes. We now show that similarly heterotypic neuronal gap junctions are abundant throughout goldfish brain, with labeling exclusively for Cx35 in presynaptic hemiplaques and exclusively for Cx34.7 in postsynaptic hemiplaques. Moreover, the vast majority of these asymmetric gap junctions occur at glutamatergic axon terminals. The widespread distribution of heterotypic gap junctions at glutamatergic mixed synapses throughout goldfish brain and spinal cord implies that pre- vs. postsynaptic asymmetry at electrical synapses evolved early in the chordate lineage. We propose that the advantages of the molecular and functional asymmetry of connexins at electrical synapses that are so prominently expressed in the teleost CNS are unlikely to have been abandoned in higher vertebrates. However, to create asymmetric coupling in mammals, where most gap junctions are composed of connexin36 (Cx36) on both sides, would require some other mechanism, such as differential phosphorylation of connexins on opposite sides of the same gap junction or on asymmetric differences in the complement of their scaffolding and regulatory proteins.